Worldviews and trust of sources for health information on electronic nicotine delivery systems: Effects on risk perceptions and use. (December 2017) - Weaver, Scott R.; Jazwa, Amelia; Popova, Lucy; Slovic, Paul; Rothenberg, Richard B.; Eriksen, Michael P.
Abstract: Public health agencies, the news media, and the tobacco/vapor industry have issued contradictory statements about the health effects of electronic nicotine delivery systems (ENDS). We investigated the levels of trust that consumers place in different information sources and how trust is associated with cultural worldviews, risk perceptions, ENDS use, and sociodemographic characteristics using a nationally representative sample of 6051 U.S. adults in 2015. Seventeen percent of adults were uncertain about their trust for one or more potential sources. Among the rest, the Centers for Disease Control and Prevention (CDC), health experts, and the Food & Drug Administration (FDA) elicited the highest levels of trust. In contrast, tobacco and vapor manufacturers, vape shop employees, and, to a lesser extent, the news media were distrusted. Adults who had higher incomes and more education or espoused egalitarian and communitarian worldviews expressed more trust in health sources and the FDA, whereas those identifying as non-Hispanic Black or multiracial reported less trust. Current smokers, those who identified as non-Hispanic Black or other race, had lower incomes, and espoused hierarchy and individualism worldviews expressed less distrust toward the tobacco and vapor industry. Greater trust (or less distrust) toward the tobacco and vapor industry and an individualism worldview were associated with perceptions of lower risk of premature death from daily ENDS use, greater uncertainty about those risks, and greater odds of using ENDS. Public health and the FDA should consider consumer trust and worldviews in the design and regulation of public education campaigns regarding the potential health risks and benefits of ENDS. Highlights: The CDC, health experts, and FDA are mostly trusted for information about ENDS. The tobacco/vapor industry and news media were mostly distrusted. Worldviews were associated with whom people trust for information about ENDS. Trust of the tobacco/vapor industry was associated with less perceived risk of ENDS. Trust and worldviews should be considered in designing public education campaigns.